1999
DOI: 10.1001/archneur.56.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic Status in Multiple Sclerosis After Treatment With Glatiramer

Abstract: Our 2-year longitudinal study showed no effect of glatiramer therapy on cognitive function in relapsing-remitting MS. Although it is possible that glatiramer therapy has no effect on cognitive function, the lack of measurable decline in cognitive function in both patient groups for 2 years limits the opportunity for glatiramer to demonstrate a therapeutic effect by minimizing such decline. Emerging treatments for MS should continue to be examined for their effect on cognitive impairment because it can be a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 50 publications
2
80
1
6
Order By: Relevance
“…If the observed increases in FA persist for longer follow-up times, it is possible that natalizumab-induced improvement and/or stabilizations in brain tissue could affect cognitive function in these patients, given the strong correlation between the severity of FA abnormalities and overall cognition found in our data, as well as in other previous studies 5,7,38 and the previously shown slow rate of cognitive decline in MS. 39 It is currently unclear, however, whether this could be in the form of actual increases in cognitive scores or merely the slowing down of cognitive decline. Therefore studies with longer follow-up times are needed.…”
Section: Discussionmentioning
confidence: 99%
“…If the observed increases in FA persist for longer follow-up times, it is possible that natalizumab-induced improvement and/or stabilizations in brain tissue could affect cognitive function in these patients, given the strong correlation between the severity of FA abnormalities and overall cognition found in our data, as well as in other previous studies 5,7,38 and the previously shown slow rate of cognitive decline in MS. 39 It is currently unclear, however, whether this could be in the form of actual increases in cognitive scores or merely the slowing down of cognitive decline. Therefore studies with longer follow-up times are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively poor spatial WM in SPMS and RRMS compared with PPMS is in agreement with findings from other studies. 3,7,13 Despite the fact that poor verbal fluency and poor higher-order WM memory operations have been shown in RRMS before, 5,6,14 poor verbal fluency in RRMS relative to PPMS contrasts earlier findings. 12 Our result does appear to be robust, considering the fact that it remained significant after controlling for a curvilinear relationship with age.…”
mentioning
confidence: 81%
“…14 Unfortunately, MS patients with progressive phenotypes were not included in the studies reporting higher-order cognitive processing deficits in RRMS, 5,6,14 whereas other studies included only the progressive subtypes. 3,7 The current study re-evaluates differences in cognitive profile between all three MS subtypes using relatively large samples for each subtype and compares performance with that of healthy control subjects.…”
mentioning
confidence: 99%
“…The effect of glatiramer acetate (GA) on cognition was evaluated as part of a phase III trial on RRMS where patients were randomized to receive GA (20 mg subcutaneously every day) or placebo [14]. Two hundred forty-eight patients were assessed by the BRNB at baseline and after 1-2 years using.…”
Section: Disease Modifying Treatmentsmentioning
confidence: 99%